The impacts of Triple-A supply chain on supply chain performance in Ethiopian textile share company - Endris Ali (Goodwood Publishing, 2021)
Purpose: This work aimed to investigate the impact of triple-A supply chain (SC) on SC performance in Bahir Dar & Kombolcha textile Share Company, Ethiopia. Research Methodology: The study used survey questionnaires as a data collection instrument. Statistical package for social science to purify measurement items & Partial least square structural equation model used to test whether SC agility, SC adaptability, and SC alignment have individual or joint effects on SC performance. Results: The finding indicates that SC adaptability, SC alignment, and SC agility have a significant effect on SC performance. The result also indicates that the joint triple-A SC had a strong impact on SC performance. Limitations: The study focused on two Ethiopian textile share companies and it does not include other companies in the country. Contribution: This study allows us to understand the joint triple-A SC, SC agility, adaptability, and SC alignment-SC performance relationships at a dimensional level and helps to develop a comprehensive research model.